Lean Semesters : How Higher Education Reproduces Inequity - Nzinga-Johnson, Sekile, 1971- (Book collections on Project MUSE., 2020)
"Neoliberal practices of the contemporary university cause disproportionate economic hardships for women, especially those who are students or adjuncts, are members of racialized groups, belong to underpaid disciplines, or are employed at less prestigious institutions. Lean Semesters addresses the reality that women of color, particularly Black women, are vulnerable to compounded forms of exploitation and inequity as faculty members"--